2008
DOI: 10.1002/dvdy.21454
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning from egg to embryo: Triggers and mechanisms of egg activation

Abstract: The transition from mature oocyte to developing embryo requires a coordinated series of events, collectively known as egg activation. Egg activation includes changes to egg coverings to prevent polyspermy, release of oocyte meiotic arrest, generation of haploid female and male pronuclei, changes in maternal mRNAs and protein populations, and cytoskeletal rearrangements. In many animals, egg activation is triggered by fertilization, which increases intracellular calcium within the oocyte and thereby regulates m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
177
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(186 citation statements)
references
References 219 publications
(249 reference statements)
4
177
0
1
Order By: Relevance
“…This A23187-enhanced Ca 2+ transport within the oocyte is mediated through a single, large Ca 2+ rise rather than the smaller, naturally repeating Ca 2+ oscillations [10,18]. Although previous studies have shown the benefit of using Ca 2+ ionophore with ICSI to enhance Ca 2+ -induced activation of mature oocytes fertilized with 2 Immunofluorescence analysis of PLC-ζ located in the male sperm.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This A23187-enhanced Ca 2+ transport within the oocyte is mediated through a single, large Ca 2+ rise rather than the smaller, naturally repeating Ca 2+ oscillations [10,18]. Although previous studies have shown the benefit of using Ca 2+ ionophore with ICSI to enhance Ca 2+ -induced activation of mature oocytes fertilized with 2 Immunofluorescence analysis of PLC-ζ located in the male sperm.…”
Section: Discussionmentioning
confidence: 95%
“…As a crucial sperm protein governing Ca 2+ -dependent oocyte activation, PLC-ζ released into the oocyte during sperm-oocyte membrane fusion [2] acts on phosphatidylinositol 4,5-biphosphate (PIP 2 ) [18] to induce its hydrolysis forming the second messengers inositol 1,4,5 triphosphate (IP 3 ) and diacylglycerol (DAG) [18]. Subsequent IP 3 binding to its own receptor on the endoplasmic reticulum (ER) [19] opens Ca 2+ channels, which release Ca 2+ from the ER into the cytoplasm of the oocyte [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oocytes are subsequently ovulated and reach a second arrest point (metaphase of meiosis II in mammals). The developed oocytes are now referred to as eggs and are competent for fertilization (13,14). In mammals, sperm interact with the egg on multiple levels (16); here we will focus only on the interactions between the sperm and egg plasma membrane.…”
Section: Fertilization and The Oocyte-to-embryo Transitionmentioning
confidence: 99%
“…Fertilization in C. elegans shares many characteristics with mammalian fertilization, including the need for sperm activation in the female reproductive tract, internal fertilization and multiple egg activation events including a membrane block to polyspermy, cortical granule (CG) exocytosis, meiotic resumption, and activation and degradation of selected maternal mRNAs and proteins (Table 1) (1,8,13). In this review, we will discuss C. elegans as a model system for fertilization and the oocyte-to-embryo transition.…”
Section: Introductionmentioning
confidence: 99%